Sosialisasi Manajamen Literasi Bahasa di Sekolah Dasar - Nuriyanti, Risma; Gumilar, Abih; Muslihah, Neni Nadiroti; Asyari, Lutfi; Gunawan, Dani; Adiredja, Rajji Koswara (IPI Press, 2025)
This article aims to provide information regarding community service activities related to efforts to socialize language literacy management in elementary schools. This socialization is a form of language literacy education and counseling for prospective elementary school teacher students with the aim of making them aware of language literacy management in elementary schools. The method used in this activity includes delivering material through lectures and questions and answers. The results achieved in this activity are students' understanding of language literacy in elementary schools which includes the meaning of language literacy, the importance of language literacy. At the end of the article, the author explains aspects of language literacy management that schools need to pay attention to in order to implement the literacy movement in elementary schools.